Processo de compra móvel: um passo participativo para avaliação cooperativa da usabilidade em aplicativo de m-commerce para smartphones - Matos, Silvia Aparecida de Oliveira de Alencar (2014)
Motivados pela descoberta em literatura de que usuários revelavam relutância em comprar via aplicativos móveis (m-commerce) em smartphones, tivemos como primeira intenção utilizar a técnica de Avaliação Cooperativa com usuários para investigar a usabilidade nestes ambientes de compra. Uma das etapas da Avaliação Cooperativa é a elaboração de uma lista de tarefas que o usuário deve realizar para avaliar a interface. Fez-se necessário, então, definir as tarefas que deveriam compor a avaliação de usabilidade. Procuramos, sem êxito, um processo de compra em aplicaivos para smartphones a fim de definir quais tarefas deveriam ser testadas pelos usuários. Encontramos, em literatura, somente processos de compra para sites. Com a participação de usuários adaptamos, então, um dos processos de compra para sites ao contexto do site da Livraria Saraiva, objeto eleito para viabilizar o nosso estudo. Com este novo processo de compra para o contexto do site da Livraria Saraiva, verificamos se as etapas de compra eram correspondentes àquelas referentes ao aplicativo móvel para smartphones da mesma livraria. Verificadas as discrepâncias, finalmente propusemos, junto com usuários, um processo de compra móvel em aplicativos para smartphones no ambiente da Livraria Saraiva. A partir deste diagrama, fizemos uma Avaliação Cooperativa no aplicativo de m-commerce da referida livraria. Este trabalho resultou na elaboração, com a participação dos usuários, de um processo de compra considerando as etapas de compra que refletissem a forma de comprar dos usuários, quando estão diantes da interface de aplicativos móveis de m-commerce desenvolvidas para smartphones, o que orientou a avaliação da usabilidade na interface do aplicativo móvel de m-commerce da Livraria Saraiva e, poderá servir a outros estudos, tanto como base metodológica quanto como diagrama de aplicação em interfaces análogas. Ainda, os resultados nos fizeram concluir que incluir os usuários na avaliação de interfaces deve, se possível, também pressupor a inclusão dos mesmos no ajuste dos parâmetros dos instrumentos que serão usados na avaliação. ABSTRACT: We were motivated to do this work because we have found in literature about m‑commerce most users revealed reluctance to buy via mobile applications in smartphones. At first we meant to use the technique of cooperative evaluation with users to investigate the usability of these shopping environments in mobile applications to smartphones. One of the steps of cooperative evaluation is the preparation of a tasks list which the user must do to evaluate the interface. It was necessary, then, to define the tasks which should compose the usability evaluation. A purchasing process in applications for smartphones was seeked, unsuccessfully, in order to define which tasks should be tested by the users. In the wide information source we only found site´s process of purchase. We made some changes for sites in the purchasing context of the site of Saraiva Bookstore with the participation of users, then, the elected object to enable this study. With this new diagram for the context of Saraiva Bookstore's site, it was checked if the steps were corresponding in the mobile application for smartphones of the same bookstore. The discrepancies were verified and it was proposed, with the users, a diagram for the purchasing process in applications for smartphones in Saraiva bookstore's shopping environment. Based on this diagram we have defined which tasks should be tested by users and the cooperative evaluation was made in the application of m-commerce of this bookstore. This work led to the development, with the users, of a diagram with purchasing steps and these steps reflected the way users purchase when they were faced to m-commerce mobile applications developed for smartphones. The purchase process diagram guided the cooperative evaluation with the application of m‑commerce studied and helped us to conclude that including users in the evaluation of interfaces should, if possible, also mean to include them in the construction of their own instruments. This led to the develop steps of purchasing process, with the participation of the users considering buying which reflected the way users buy when they have to use m‑commerce applications developed for smartphones mobile interface and this guided the evaluation of the usability of mobile application m-commerce Saraiva interface. This study may be applied to other studies, both as a methodological basis and as well as a diagram analogous application interfaces. Still, the results have made us conclude including users in the evaluation of interfaces should, if possible, also assume their inclusion in adjusting the parameters of the instruments which will be used in the evaluation of the interface.